356 Microsurgical Anatomy of the Brainstem Safe Entry Zones: A Cadaveric Study With High-Resolution Magnetic Resonance Imaging and Fiber Tracking. (1st August 2016) - Mukherjee, Debraj; Antar, Veysel; Gurer, Bora; Cikla, Ulas; Neves, Gabriel; Ekici, Mehmet; Hananya, Tomer; Field, Aaron S.; Salamat, Shahriar M.; Baskaya, Mustafa Kemal
Abstract: INTRODUCTION: Operative management of intrinsic brainstem lesions remains challenging despite advances in electrophysiological monitoring and neuroimaging. Surgical intervention in this region requires detailed knowledge of adjacent, critical white matter tracts and cranial nerve nuclei. Our aim was to systematically verify internal anatomy associated with each brainstem safety zone entry zone (BSEZ) using a cadaveric model supplemented with neuroimaging modalities commonly used in preoperatively planning, namely high-resolution magnetic resonance imaging (MRI) and fiber tracking. METHODS: Twelve BSEZs were simulated in 8 formalin-fixed, cadaveric heads. Specimens then underwent radiological investigation including T2-weighted imaging and fiber tracking using 4.7 T MRI. The distance between simulated BSEZs and predefined, adjacent, critical structures was systemically recorded. RESULTS: Entry points and anatomic limits on the surface of the brainstem are described for each BSEZ, along with description of neurological sequelae if such limits are violated. With high-resolution imaging, we verified maximal depth and optimal angle of entry for each BSEZ. The relationship between BSEZs and adjacent, critical structures was quantified. Orbitozygomatic, suboccipital, retrosigmoid, retrolabyrinthine, and petrosectomy approaches were used to simulate BSEZs in the ventral, dorsal, and lateral brainstem. Critical structures most at risk for injury during BSEZ approach included the oculomotor nerve, trochlear nerve, red nucleus, medial lemniscus, medial longitudinal fasciculus, corticospinal tract, and hypoglossal nucleus. CONCLUSION: Once thought to be universally inoperable, select lesions of the brainstem may now be treated by experienced surgeons with adjunct instrumentation, imaging, neuromonitoring, and intricate knowledge of BSEZs. All approaches adhered to the 2-point rule while minimizing neural and vascular damage. In combination with cadaveric dissection, high-resolution MRI and fiber tracking allow the surgical team to develop a better understanding of the internal architecture of the brainstem, particularly as related to BSEZs. The careful study of such imaging may lead to more accurate and safe surgery through use of optimal surgical corridors.